Higher Risk of Hepatocellular Carcinoma Progression in the Population of Untreated Immune-Tolerant Phase Chronic Hepatitis B Patients: An Evidence Based - Alessa Fahira; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2020)
Background: Hepatitis B infection is a major health problem worldwide, currently occurring in 350-400 millions of people. If not treated properly, hepatitis B infection may progess into chronic hepatitis B (CHB)—which may developed into hepatocelullar carcinoma (HCC). The first phase of CHB, the immune-tolerance (IT) phase, is marked with minimal necroinflammatic activity and a lower risk in the development of a more chronic liver condition, by hence antiviral therapy is not recommended. Recent studies however, shows that there are apparently histological activity and immune specific response towards HBV, accompanied by extensive clonal expansion of hepatitis in the IT phase, hence questioning its risk for the development of HCC. This evidence-based case report is meant to comprehensively review the effect of antiviral treatment in IT-phase CHB patients from available studies.Method: Pubmed, ProQuest, Cochrane, Scopus, Sciencedirect and EBSCOhost were comprehensively searched for systematic review and cohort prognostic researches studying the impact of anti-virals treatment for CHB patients in IT-phase. Three studies were selected and critically appraised. Data were then summarized descriptively.Results: The three studies included in this study were retrospective cohort studies. One study stated that the treated IT-phase group had significantly reduced risk for HCC (HR = 0.234; log-rank p = 0.046), compared to the untreated IT-phase group. One study found that untreated IT phase is asscociated with significantly higher risk of HCC (HR = 2.54; 95% CI: 1.54 to 4.18; p 0.001) compared to the treated immune-active (IA) phase group. The last study stated a higher adjusted hazard ratio (aHR) of the UIT in predicting HCC risk was 2.327 (95% CI 0.475–11.391; p = 0.297), if compared to the IA group.Conclusion: While studies shows apparent results regarding the treatment of CHB patients in the IT-phase and its benefit in reducing cumulative incidence of HCC, its clinical advantage is soon to be discovered. The results were inconclusive, and the initiation of treatment in CHB patients within the IT-phase cannot yet be recommended until further research.